2008
DOI: 10.1097/ede.0b013e31816a1cff
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Birth Order and Maternal Age on Breast Cancer Risk

Abstract: These findings suggest that early life risk factor associations for breast cancer may differ according to breast-feeding status in infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Milk-formula fed girls had greater mean ovarian volumes and a greater number of follicles per cyst per ovary than breast-fed girls, while milk formula-fed boys had lower mean testicular volumes than breastfed boys (Gilchrist et al 2010). Other studies examining the effects of breastfeeding on long-term reproductive health have found that exposure to breast milk in infancy is associated with later age at menarche (Ong et al 2009), lower estrogen and testosterone levels in adulthood (Laustsen et al 2011), and slightly lower breast cancer risk in adulthood (Borgert et al 2003; Nichols et al 2008). While the mechanisms linking breastfeeding to later reproductive outcomes remain to be elucidated, our results suggest that breastfeeding is associated with lower endogenous estrogen production in girls and boys, but higher testosterone production in boys during infancy.…”
Section: Discussionmentioning
confidence: 99%
“…Milk-formula fed girls had greater mean ovarian volumes and a greater number of follicles per cyst per ovary than breast-fed girls, while milk formula-fed boys had lower mean testicular volumes than breastfed boys (Gilchrist et al 2010). Other studies examining the effects of breastfeeding on long-term reproductive health have found that exposure to breast milk in infancy is associated with later age at menarche (Ong et al 2009), lower estrogen and testosterone levels in adulthood (Laustsen et al 2011), and slightly lower breast cancer risk in adulthood (Borgert et al 2003; Nichols et al 2008). While the mechanisms linking breastfeeding to later reproductive outcomes remain to be elucidated, our results suggest that breastfeeding is associated with lower endogenous estrogen production in girls and boys, but higher testosterone production in boys during infancy.…”
Section: Discussionmentioning
confidence: 99%
“…The CBCS is a population based case-control study that was carried out in Wisconsin, Massachusetts (apart from metropolitan Boston), Maine and New Hampshire (1618). Eligible case subjects were women identified by each state’s cancer registry with a new breast cancer diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Although some studies including prospective studies have demonstrated no association [22-24, 26, 38, 39], four case-control studies have suggested a protective effect of being breastfed [19][20][21]25]. Some studies have also evaluated breast cancer risk in terms of menopausal status [19,25,26,39].…”
Section: Discussionmentioning
confidence: 96%
“…Some case-control studies showed a protective effect of being breastfed [19][20][21], whereas recent prospective studies reported no overall association [22][23][24]. With regard to menopausal status, a case-control study by Barba et al.…”
Section: Introductionmentioning
confidence: 94%